Cause and effect : intermediate reading practice with answers - Ackert, Patricia; Navarro, Nicki Giroux de.; Bernard, Jean.; Ban biên dịch First News. (Tp.HCM : Nxb Trẻ, 2004)
Explorers; World issues; A mishmash (a hodgepodge); Science; Medicine and health.
Keywords: Anh ngữ; English language; English language -- Reading -- Study and teaching